Audit of discharges from a regional service in the United Kingdom. Issue 1 (17th June 2013) - Phillipson, Adrian; Akroyd, Mike; Carley, Joanne
Abstract Aim As early intervention in psychosis (EI) continues to develop, clinical governance maintains an important role in the 'real world' analysis of services. This paper details an audit of all discharges from a regional early intervention service in the United Kingdom, providing benchmarking information on service structure, interventions and outcomes. The background places the service in the context of national and international guidelines. Methods All discharges between service inception in 2004 and February 2011 were retrospectively examined and audited according to identified standards, based upon international and national guidelines. A total of 110 patients were discharged from the EI service after a period of involvement of at least 6 months. Results A high proportion of service users (55%) had their care transferred back to primary care after discharge. Physical health and social needs were well addressed, and almost half of individuals were in education, training or employment upon discharge. Most service users (69%) did not require inpatient admission during their involvement with the service. Although the majority had psychological, pharmacological and physical health needs addressed, there remained room for improvement when measured against identified standards. Conclusions This paper details outcomes of every patient seen by an EI service since inception, providing valuable benchmarking information for those involved in management of similar services, service redevelopment, commissioning, and implementation of evidence‐based practice. The proportion of service users in education, training or employment after discharge exceeded expectations considerably.